2021
DOI: 10.1177/1367877920951818
|View full text |Cite
|
Sign up to set email alerts
|

No future for care without new digital media? Making time(s) for mediated informal care practices in later life

Abstract: There is a growing interest in using social media and digital platforms as allies to strengthen social support among the aged. Drawing on ethnographic interviews and observations of 21 people in their 80s, the article foregrounds the multiple and intersecting temporalities of informal mediated care practices in later life through an exploration of the wide range of infrastructures on which they rely, from social media platforms to housing and urban infrastructure. We identify four temporalities of mediated inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…So far, studies have dealt with the impact of social media use and interventions on carers' mental health and well-being (Cherak et al, 2020), as well as the possible benefits of the use of social media for carers (for example, social support) (López-Gómez et al, 2021), but in terms of media representations of male carers, we identified a lack of scientific studies. In a study on a children's television programme focused on media representations of care, Inthorn (2018) found that while positive aspects of care were addressed, adult informal care remained gendered.…”
Section: Media Representation Of Male Carersmentioning
confidence: 99%
“…So far, studies have dealt with the impact of social media use and interventions on carers' mental health and well-being (Cherak et al, 2020), as well as the possible benefits of the use of social media for carers (for example, social support) (López-Gómez et al, 2021), but in terms of media representations of male carers, we identified a lack of scientific studies. In a study on a children's television programme focused on media representations of care, Inthorn (2018) found that while positive aspects of care were addressed, adult informal care remained gendered.…”
Section: Media Representation Of Male Carersmentioning
confidence: 99%